Scoping Review: Intervensi Penyakit Tidak Menular Menggunakan Media Digital Promosi Kesehatan dalam Proses Pencegahan Primer - Irto Titus; Mohammad Zen Rafiludin; Cahya Tri Purnami (Jurnal Rekam Medis dan Informasi Kesehatan, 2024)
Every year, 17 million people die from NCDs before the age of 70; 86% of these premature deaths occur in low- and middle-income countries. Changes in digital media are taking place so fast that health education in health counseling must need to be updated by doing a new innovation so that it can create a health promotion media product that can be consumed by the public easily. Objective: to map the literature on a particular topic or research and provide an opportunity to identify key concepts, gaps in research, and for policy making. Methods: the process of finding relevant reviews we used literature sources obtained through searches using PubMed, Scopus, Sciencedirect and Google Scholar databases and Global Health. Results: We reviewed 1165 studies from 10 databases, the results of the review we got 780 studies after that we filtered and got 491 full text articles, and the end of the full text filter we got 13 research articles in the inclusion category and will then be reviewed for the scoping review.